Influencing factors on the quality of recovery after total knee arthroplasty: development of a predictive model - Shan, Sen; Shi, Qingpeng; Zhang, Hengyuan (Frontiers in Medicine, 2024)
Total Knee Arthroplasty (TKA) significantly benefits patients with severe knee degeneration, though postoperative recovery outcomes can vary widely. In a retrospective analysis of 362 TKA cases from January 1, 2018, to July 1, 2022, this study identified factors influencing recovery in the first year after surgery. Using multivariate logistic regression, we found key predictors of poor recovery: Body Mass Index (BMI), age-adjusted Charlson Comorbidity Index (aCCI), sleep quality, Bone Mineral Density (BMD), and analgesic efficacy (p<0.05). These factors were used to create a clinical prediction model with an Area Under the Receiver Operating Characteristic (AUC) curve of 0.802, validated internally. The study highlights the potential for personalized postoperative care and tailored rehabilitation programs to optimize recovery outcomes and enhance patient satisfaction.